2020
DOI: 10.1037/pas0000801
|View full text |Cite
|
Sign up to set email alerts
|

Spanish validation of the short-form of the Avoidance and Fusion Questionnaire (AFQ-Y8) with children and adolescents.

Abstract: The Avoidance and Fusion Questionnaire for Youth-Short Form (AFQ-Y8) was designed to measure psychological inflexibility in children and adolescents. However, it has not yet been validated to the Spanish population. The present study examines the factorial structure, internal consistency, convergent and incremental validity, and measurement invariance between children and adolescents, male and female, and male and female across age of the AFQ-Y8 with 982 students from Spain (children ϭ 459, adolescents ϭ 523).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
0
9
0
6
Order By: Relevance
“…The total score ranges from 0 to 32 with higher scores reflecting a higher degree of avoidance and fusion. Recent studies show that AFQ-Y8 is a reliable and valid measure of these elements of psychological inflexibility in children and adolescents [79,80].…”
Section: Measures Of Treatment Targetsmentioning
confidence: 99%
“…The total score ranges from 0 to 32 with higher scores reflecting a higher degree of avoidance and fusion. Recent studies show that AFQ-Y8 is a reliable and valid measure of these elements of psychological inflexibility in children and adolescents [79,80].…”
Section: Measures Of Treatment Targetsmentioning
confidence: 99%
“…A possible explanation for this difference is that our sample was younger than the sample in the original validation study. A recent validation of the brief format version of the questionnaire (the AFQ-Y8) [ 34 ] found that young children score lower than adolescents. This is compatible with the existing evidence that the frequency and intensity of negative emotions increase with age during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…The very ample research with adult samples has shown that PI strongly predicts emotional distress, psychopathology, and poor mental health and quality of life [ 28 , 29 , 30 , 31 , 32 , 33 ]. Research with children and adolescents is less abundant, but nonetheless, the available evidence shows that PI is associated with both externalizing and internalizing mental health problems, particularly with symptoms of anxiety and mood disorders [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spanish-speaking samples are growing increasingly represented in the psychological testing literature, as reflected by the establishment of the Journal of Latinx Psychology (formerly the Journal of Latina/o Psychology ) in 2012 and special editorial sections related to research on translated instruments in journals like Psychological Assessment (e.g., Lima et al, 2017 ; Silva et al, 2018 ; García-Rubio et al, 2020 ). This increased focus on psychological assessment in Spanish mirrors growing awareness that ethnically and racially diverse samples are essential to generalizable psychometric research.…”
Section: Introductionmentioning
confidence: 99%